Proteome and Phosphoproteome Analyses Reveal the Kinase Regulatory Network Involved in Glycogen Synthesis Kinase 3β - Hu, Mingyang; Fang, Jiuyuan; Wang, Huijuan; Zhou, Sijie (Frontiers in Genetics, 2021)
Diabetic nephropathy is the most common chronic kidney disease in the world and the main cause of end-stage renal disease (ESRD). The structural integrity of podocytes is fundamental to the normal function of the glomerulus, and the role of glycogen synthase kinase 3β (GSK-3β) in podocytes is complicated. A thorough understanding of GSK-3β is crucial to understand the mechanism of diabetic nephropathy. To analyze the roles of GSK-3β in podocytes, GSK-3β knockdown lentivirus by Clustered regularly interspaced short palindromic repeats (CRISPR)-CRISPR-associated protein (Cas)9 was applied to establish stable cell lines. Mass spectrometry was utilized to search for differentially expressed proteins. Consequently, we found 34 proteins with higher levels and 115 proteins with lower levels in GSk-3β knockdown cells than in control cells and identified 581 phosphosites with higher phosphorylation levels and 288 phosphosites with lower phosphorylation levels. We performed functional enrichment analysis of these proteins and phosphorylated proteins based on public databases. Enrichment analysis revealed that GSK-3β participates in the spliceosome, Hippo signaling pathway, actin binding, structural molecule activity and other pathways. Then, we used motif analysis of phosphate sites to determine 89 conserved motifs based on 1068 phosphoserine (pS) sites and 15 conserved motifs in view of 104 phosphothreonine (pT) sites. Additionally, protein-protein interaction network analysis was carried out using the String database. Cytoscape's addon Molecular Complex Detection (MCODE) was used to analyze key and core protein groups. In quantitative differential protein analysis, four MCODEs were obtained, and twenty-two MCODEs were obtained in the analysis of the phosphoproteome of differentially expressed proteins. Finally, we analyzed the kinase regulatory network in podocytes after GSK-3β knockdown and identified 299 protein kinases and 3460 significantly changed phosphorylation modification sites on 1574 proteins. These results will be valuable for further research on GSK-3β.